Light and Primary Production Shape Bacterial Activity and Community Composition of Aerobic Anoxygenic Phototrophic Bacteria in a Microcosm Experiment - Kasia Piwosz (American Society for Microbiology, 2020)
ABSTRACT Phytoplankton is a key component of aquatic microbial communities, and metabolic coupling between phytoplankton and bacteria determines the fate of dissolved organic carbon (DOC). Yet, the impact of primary production on bacterial activity and community composition remains largely unknown, as, for example, in the case of aerobic anoxygenic phototrophic (AAP) bacteria that utilize both phytoplankton-derived DOC and light as energy sources. Here, we studied how reduction of primary production in a natural freshwater community affects the bacterial community composition and its activity, focusing primarily on AAP bacteria. The bacterial respiration rate was the lowest when photosynthesis was reduced by direct inhibition of photosystem II and the highest in ambient light condition with no photosynthesis inhibition, suggesting that it was limited by carbon availability. However, bacterial assimilation rates of leucine and glucose were unaffected, indicating that increased bacterial growth efficiency (e.g., due to photoheterotrophy) can help to maintain overall bacterial production when low primary production limits DOC availability. Bacterial community composition was tightly linked to light intensity, mainly due to the increased relative abundance of light-dependent AAP bacteria. This notion shows that changes in bacterial community composition are not necessarily reflected by changes in bacterial production or growth and vice versa. Moreover, we demonstrated for the first time that light can directly affect bacterial community composition, a topic which has been neglected in studies of phytoplankton-bacteria interactions. IMPORTANCE Metabolic coupling between phytoplankton and bacteria determines the fate of dissolved organic carbon in aquatic environments, and yet how changes in the rate of primary production affect the bacterial activity and community composition remains understudied. Here, we experimentally limited the rate of primary production either by lowering light intensity or by adding a photosynthesis inhibitor. The induced decrease had a greater influence on bacterial respiration than on bacterial production and growth rate, especially at an optimal light intensity. This suggests that changes in primary production drive bacterial activity, but the effect on carbon flow may be mitigated by increased bacterial growth efficiencies, especially of light-dependent AAP bacteria. Bacterial activities were independent of changes in bacterial community composition, which were driven by light availability and AAP bacteria. This direct effect of light on composition of bacterial communities has not been documented previously.